A new three-term spectral subgradient method for solving absolute value equation. Issue 2 (1st February 2023) - Rahpeymaii, Farzad; Amini, Keyvan; Rostamy-Malkhalifeh, Mohsen
Abstract : In this paper, a new three-term spectral conjugate subgradient method is presented to solve an absolute value equation. The new method is constructed based on conjugate gradient method proposed by Dai & Yuan and Barzilai & Borwein technique. In each iteration, a descent direction is generated. The global convergence of the new method is established under some mild assumptions. The numerical results are reported, showing the efficiency of our method.